Different types of nouns, different types of projections - Gondra, Ager (IBERIA: An International Journal of Theoretical Linguistics, 2014)
This paper proposes (1) for Basque nominal domain. Expanding on the ideas of Distributed Morphology, all nouns are syntactically derived from a categorically unspecied root, which is nominalized by an n-head. With deverbal nouns, this unspeci ed root is rst dominated by a series of structure-creating nodes (V-v). Event nouns take an external and an internal argument due to their argument structure, and have an event reading, while result nouns have the option to take an adjunctexternal argument and an internal argument, and have a referential reading. Thus, event nouns project the v that introduces the event reading and the external argument, while result nouns project a defective v* that has a non-active reading and does not introduce an external argument (Kratzer 1996). With common nouns, however, the »RP merges directly with the little n, making impossible for them to take arguments. Finally, with result nouns and common nouns, a possessor1 is possible. Hence, two types of n are proposed: n* introduces the possessor, while n does not. The possessor raises to the Spec-FP position along with the external and the internal argument.